Secondary EFL Teachers’ Views Towards the Implementation of Peer Assessment: Between Opportunities and Challenges - Fatma Rahayu Nita; Syafi'ul Anam (ELT Worldwide: Journal of English Language Teaching, 2021)
As the previous studies lack proof of teachers' experience and perceptions, especially in secondary school; thus, this current study concerns teachers’ knowledge of the implementation of peer assessment. This study attempts to answer the three research questions: (1) What are EFL teachers' perceptions and experiences towards implementing peer assessment in speaking skills? (2) What are the reasons EFL teachers utilize peer assessment in speaking skills? (3) What are the obstacles faced by EFL teachers in using peer assessment in speaking skills? This current study employed a qualitative approach. It examined the narratives of eight teachers who give responses on the questionnaire and a virtual interview. The results reveal that most teachers gain positive experience in implementing peer assessment in the classroom. It sheds light on three themes of opportunities and five pieces of challenges that have been matched with the literature. Eight teachers encounter more challenges since they don’t commonly use peer assessment in the class. Most importantly, a peer assessment provides an opportunity to enhance student’s learning, and it should be applied to give a chance for the students to develop their skills. Therefore, educational institutions for secondary EFL teachers should consider incorporating peer assessment into their instructional designs so that they are experienced and make peer assessment a precious alternative to language assessment.